MAKNA HIDUP DI BAUK TRADISI MUDIK LEBARAN (STUDI FENOMENOLOGI ATAS PENGALAMAN PEMUDIK DALAM MERAYAKAN IDUL FITRI DI KAMPUNG HALAMAN) - Muskinul Fuad (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2011)
Mudik lebaran(visiting hometown on Idul Fitri Days) is an annual tradition which is never left by most urban people who are originallyfrom smalleror othertown. Some days before Idul Fitri day, we can see how crowded the traffic is. It is a unique phenomenon of Idul Fitri which is especially found in Indonesia. Lebaran/ Idul fitri is a specific example about how Islamic idioms are creatively intrepreted in Indonesian culture. This unique and specific example of lebaran in Indonesia can be seen not only on the phenomenon of mudik but also on the situation and idioms such as takbiran, shaking hands, sungkeman, halal bi halal, ziarah kubur (visit cemetery) before lebaran and before the month of Ramadhan (nyadran), lebaran banquet, giving some moneytochildren, etc. Besidesthe explanation ofthe meaning of lebaran from normative sides, it is necessary to reveal the subjective meaning of lebaran tradition. This research revealed those meanings through phenomenological perspedive and analyzed them with psychoanalysis. Using the logotherapytheory of Viktor Frankl, it was found thatthe values ofthe tradition to go hometown during Idul Fitri days helped them to find the meaning of life. The values or meanings which could be found are: the meaning of family relatives and its education valueforthe family, existence meaning, primordial meaning, and transformative meaning. Those meanings indeed are very beneficial forthem as a therapyto revitalizetheir individual and social lives. Mudik can improvetheir mental health and bring happiness.